(untitled) (Journal of Small Business Strategy (archive only), 1990)
The Export-Import Ban·k of the United States (Eximbank) operated a pilot program with sei'en state and city agencies d uring 1988. That institution sought to determine if a partnership with such local agencies could assist small firms to acquire export-finance support needed to secure international marketing transactions. This pa per evaluates achievements and requirements as the pilot effort is converted into a permanent cooperative program in 1989.